Pengaruh Faktor Eksternal pada Masa Kemunduran Islam Periode Pertama (1250-1500 M) - Soraya Zairina Asmadi; Haidar Putra Daulay; Solihah Titin Sumanti (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2025)
This research discusses "The Influence of External Factors During the Decline of the First Period (1250-1500 AD)". The main focus of this research is to find external factors that were behind the decline of Islam in the first period. The formulation of the problem regarding the influence of external factors during the decline of Islam in the first period is 1) What was the social condition of Muslims during the decline of Islam in the first period? 2) What were the causes of the decline of Islam in the first period due to external factors? 3) What were the impacts of the first period of Islamic decline on external factors? Through qualitative methods with a library research approach. The main data sources include books on Islamic history/culture, as well as scientific works related to the First Period of Islamic Decline. This approach allows an in-depth analysis of the influence of external factors during the first period of Islamic decline (1250-1500 AD) which is relevant to related history books.